Psychological mediators between risk perception and psychological wellbeing in emergency healthcare workers - Badía, Maria del Carmen; Alarcón, Rafael; Trillo, Javier; Miranda-Páez, Jesús (Frontiers in Psychology, 2024)
Healthcare workers are subjected to numerous work-related stress factors, which have negative consequences on their physical and mental health, making them a vulnerable group. The recent pandemic caused by the new coronavirus created a high demand for attention from healthcare workers, which put their mental health at risk. This study aimed to test a mediation model in which resilience and the satisfaction of psychological needs play a mediating role in risk perception, the attitude toward the management carried out by the administration, emotional intelligence on psychological wellbeing, and depressive symptoms of frontline professionals. The sample consisted of 405 healthcare professionals aged between 22 and 65 years, belonging to critical care units in southern Spain. Linear correlation and mediation analyses were performed. The results showed that psychological wellbeing had positive correlations with resilience and negative correlations with the discrepancy in the satisfaction of psychological needs. Depressive symptoms had negative correlations with resilience and positive correlations with the satisfaction of psychological needs. To explore these results further, a mediation analysis was conducted, and a large set of significant indirect effects was found.